2016
DOI: 10.1016/j.celrep.2016.02.054
|View full text |Cite
|
Sign up to set email alerts
|

Activity-Dependent Plasticity of Spike Pauses in Cerebellar Purkinje Cells

Abstract: Summary Plasticity of intrinsic excitability has been described in several types of neurons, but the significance of non-synaptic mechanisms in brain plasticity and learning remains elusive. Cerebellar Purkinje cells are inhibitory neurons that spontaneously fire action potentials at high frequencies and regulate activity in their target cells in the cerebellar nuclei by generating a characteristic spike burst–pause sequence upon synaptic activation. Using patch-clamp recordings from mouse Purkinje cells, we f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
69
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(79 citation statements)
references
References 35 publications
10
69
0
Order By: Relevance
“…On the other hand, intrinsic plasticity may affect neuronal spike output independent from synaptic plasticity. For example, SK channel-dependent intrinsic plasticity reduces the duration of spike pauses in Purkinje cells and may thus alter the spike output of the cerebellar cortex without any synaptic involvement in the expression phase of this plasticity mechanism (Grasselli et al, 2016; Fig. 3).…”
Section: Intrinsic Plasticity: Cellular Mechanisms and Relevance To Lmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, intrinsic plasticity may affect neuronal spike output independent from synaptic plasticity. For example, SK channel-dependent intrinsic plasticity reduces the duration of spike pauses in Purkinje cells and may thus alter the spike output of the cerebellar cortex without any synaptic involvement in the expression phase of this plasticity mechanism (Grasselli et al, 2016; Fig. 3).…”
Section: Intrinsic Plasticity: Cellular Mechanisms and Relevance To Lmentioning
confidence: 99%
“…On a final note, we would like to point out that changes in intrinsic excitability can also be part of the memory trace without any involvement of synapses (other than in the induction phase). We have recently shown that intrinsic plasticity can alter the duration of spike pauses in Purkinje cells, thus changing the spike burst - pause sequence that is characteristic for the output from cerebellar cortex (Grasselli et al, 2016; Fig. 3).…”
Section: The Synapse Versus the Neuron As The Critical Site In Memorymentioning
confidence: 99%
“…As SK2 channels have been shown to underlie the medium AHP in Purkinje cells (Kakizawa et al, 2007;Grasselli et al, 2016), we looked at the AHP following a burst of 10 parallel fiber stimuli at 100 Hz. Figure 3 shows example traces for Purkinje cells from a pseudoconditioned ( Figure 3A) and a conditioned animal ( Figure 3B) following a burst of parallel fiber stimulation.…”
Section: Decreased Amplitudes Of Ahps Following Parallel Fiber Burstsmentioning
confidence: 99%
“…More recent evidence has suggested that post-complex spike pauses are regulated in an activity-dependent manner [92], which could affect the rate of CN plasticity. These findings support the idea that post-complex spike pauses train circuit changes in CN by selectively enhancing plasticity at MF to CN synapses.…”
Section: Contribution Of Climbing Fibers To Cerebellar Cortex and Cermentioning
confidence: 99%